Seguenziidae (Gastropoda: Vetigastropoda) from SE Brazil collected by the Marion Dufresne (MD55) expedition - Salvador, Rodrigo B.; Cavallari, Daniel C.; Simone, Luiz R. L. (Zootaxa, 2014)
The present work deals with the vetigastropods of the family Seguenziidae collected by the Marion Dufresne (MD55) expedition in SE Brazil, reporting the occurrence of eight species. The following species have their geographical range extended: Ancistrobasis costulata, Carenzia carinata, Carenzia trispinosa, Hadroconus altus, Seguenzia elegans and Seguenzia formosa. Two new species, Halystina umberlee sp. nov. and Seguenzia triteia sp. nov., are described.